Real-time fretting loop regime transition identification using acoustic emissions. (May 2020) - Wade, A.; Copley, R.; Clarke, B.; Alsheikh Omar, A.; Beadling, A.R.; Liskiewicz, T.; Bryant, M.G.
Abstract: Acoustic emission (AE) has been successfully used to investigate the damage mechanisms of fretting contacts within different regimes. This study investigated the transition between fretting regimes using the relationship between AE and the mechanical response of a dry, steel-on-steel, ball-on-flat contact under different tangential displacements achieving the partial slip regime, mixed fretting regime and gross slip regime. Increased AE response occurred during gross-slip events and there was strong positive correlation between AE and fretting energy ratio. The relationship was strongest when gross sliding was experienced allowing identification of transition from the partial slip to the gross slip regime. This makes AE a good candidate to detect regime transition in-situ due to ease of integration and its non-destructive nature. Highlights: Successfully measured the acoustic response of a fretting contact. Real-time correlation between the mechanical response and acoustic emission over the experiment duration. Sub-loop correlation between mechanical and acoustic events. Transition identification between fretting regimes using the acoustic response.